Plan de Gestión de los residuos sólidos peligrosos y no peligrosos generados en los laboratorios de Universidad Nacional de Loja, campus La Argelia - Moreno González, Edisson Clemente (2024)
Currently, the generation of hazardous and non-hazardous solid waste causes impacts on a local, regional, and global scale, affecting the health and integrity of living beings and the environment. Damage caused by hazardous and non-hazardous solid waste occurs in domestic, commercial, infrastructural, and institutional sectors, the latter being the main focus of this proposal for a management plan for hazardous and non-hazardous solid waste generated in the laboratories of the Loja National University, La Argelia campus. In this regard, to comply with this objective, first, the types of solid waste generated in the laboratories were identified, followed by their characterization through the calculation of weight, volume, and density. Then, a diagnosis was made to know the current management of solid waste in the stages contemplated in the RECOA (generation, storage, treatment, and transportation). A total of 11 types of hazardous solid waste were identified, which had a generation of 21.95 kg during 8 days of sampling, being the Agriculture and Renewable Natural Resources Faculty the one with the highest generation with 9.71 kg corresponding to 44%. The diagnosis identified problems in all the stages evaluated, with the separation and storage stages being the most non-compliant. Therefore, it was possibly to verify that the laboratories of the La Argelia campus generate hazardous solid waste due to the research processes carried out by students and teachers, as well as due to the inadequate solid waste management process and the poor environmental education about management strategies of these. Thanks to this, the management plan made it possible to propose programs for the management of hazardous and non-hazardous solid waste, as well as training and environmental awareness programs in accordance with current national regulations.